2014
DOI: 10.5455/jcme.20140928035119
|View full text |Cite
|
Sign up to set email alerts
|

Medical students perception on anatomy knowledge relevance and retention during clerkship

Abstract: Introduction: Sufficient knowledge of anatomy is crucial for safe and efficient clinical practice. The majority of students in the traditional, non-problem based learning curricula found anatomy taught to them in the preclinical phase irrelevant to their clinical practice. Aim: This is a cross-sectional study aiming to investigate senior medical students' perception on anatomy taught in our hybrid problem based learning curriculum, and to measure anatomy knowledge retention during clerkship. Methods: A self-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
10
2
Order By: Relevance
“…On the other hand, the results of Nabil et al demonstrated that 68% of the students strongly agreed about the importance of anatomy knowledge for their future role as physicians (25). This discrepancy in the current study between clinical and preclinical students' attitude about clinical significant of anatomy may have resulted from the insufficiency of anatomy knowledge in junior students.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…On the other hand, the results of Nabil et al demonstrated that 68% of the students strongly agreed about the importance of anatomy knowledge for their future role as physicians (25). This discrepancy in the current study between clinical and preclinical students' attitude about clinical significant of anatomy may have resulted from the insufficiency of anatomy knowledge in junior students.…”
Section: Discussioncontrasting
confidence: 52%
“…Medical students spend their first 2.5 years at the beginning of medical education on studying basic sciences, such as anatomy before being involved in their clinical clerkship (25). Anatomy has recently been undergoing some changes in medical schools of different universities, according to the demands of modern medical practice (26).…”
Section: Discussionmentioning
confidence: 99%
“…Anatomy is the cornerstone of medical education, providing a background knowledge that is essential for all medical careers. 17 In our study, clinicians and students showed moderately high positive attitudes towards anatomical knowledge with a mean score of 31.4 (±3.4) and 30.7 (±4.4), respectively, representing 76.7% to 78.3%. Besides, there was no statistically significant difference between males and females in terms of their attitude towards anatomical knowledge among the two study populations.…”
Section: Discussionmentioning
confidence: 49%
“…Although these resources are indispensable to gain knowledge, studies show that 3D online atlases could further aid to develop concepts of anatomical relations. 7,8 Moreover, learners less adept in spatial interpretation find it difficult to learn solely from two-dimensional resources like text books 4 . Plastic models are a good option to study anatomy in 3D, however, good quality and detailed versions of these are expensive and have limited availability.…”
Section: Introductionmentioning
confidence: 99%